Reform of state-owned enterprises and privatisation : a dialogue - Sobhan, Rehman; Akash, M. Mokaddem; Akram, Tanweer; Centre for Policy Dialogue (Bangladesh); World Bank.; International Dialogue on Reform of State-owned Enterprises and Privatisation (1996 : Centre for Policy Dialogue) (Dhaka : Pathak Shamabesh, 1998)
Contributed articles presented at an International Dialogue on Reform of State-owned Enterprises and Privatisation, jointly organised by the Centre for Policy Dialogue and World Bank on 2nd and 3rd November 1996.
ESS
Keywords: Government business enterprises -- India -- Congresses; Privatization -- India -- Congresses; Land reform -- India -- Congresses